Mesoporous block copolymer nanoparticles with tailored structures by hydrogen-bonding-assisted self-assembly - Deng, Renhua (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.